Transcriptomics of human multipotent mesenchymal stromal cells: Retrospective analysis and future prospects - Kasoju, N; Wang, H; Zhang, B; George, J; Gao, S; Triffitt, J; Cui, Z; Ye, H (Elsevier, 2017)
The plastic-adherent, fibroblast-like, clonogenic cells found in the human body now defined as multipotent “Mesenchymal Stromal Cells” (MSCs) hold immense potential for cell-based therapies. Recently, research and basic knowledge of these cells has fast-tracked, both from fundamental and translational perspectives. There have been important discoveries with respect to the available variety of tissue sources, the development of protocols for their easy isolation and in vitro expansion and for directed differentiation into various cell types. In addition, there has been discovery of novel abilities such as immune-modulation and the further development of the use of biomaterials to aid isolation, expansion and differentiation together with improved delivery to the selected optimal tissue site. However, the molecular fingerprint of MSCs in these contexts remains imprecise and inadequate. Consequently, without this crucial knowledge it is difficult to achieve progress to determine with precision their practical developmental potentials. Detailed investigations on the global gene expression, or transcriptome, of MSCs could offer essential clues in this regard. In this article, we address the challenges associated with MSC transcriptome studies, the paradoxes observed in published experimental results and the need for careful transcriptomic analysis. We describe the exemplary applications with various transcriptome platforms that are used to address the variation in biomarkers and the identification of differentiation processes. The evolution and the potentials for adapting next-generation sequencing (NGS) technology in transcriptome analysis are discussed. Lastly, based on review of the existing understanding and published studies, we propose how NGS may be applied to promote further understanding of the biology of MSCs and their use in allied fields such as regenerative medicine.